BENTUK DAN MAKNA PENAMAAN TEMPAT DI KECAMATAN JAWAI KABUPATEN SAMBAS - Permata, Canty; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe naming of places in JawaiSub-district has its own characteristics contained the origin of the name of the place.. It is important to know the name in each place. However, not everyone who lives un other place knows the origin of name of place that has been given.Naming places is closely related to geographical and cultural conditions in each region. The naming of places is not only seen geographically and culturally, but is formed through past stories, the conditions of previous societies and the languages used in each region both Chinese, Dayak, Malay and Javanese. Therefore, to solve this problem the researcher details the problem, namely how the form and meaning of naming the place in Jawai District, Sambas Regency. the results of the study obtained 20 place name data which were grouped into seven categories, namely based on plants, geography, location, people's names, occupation, people's actions, and stories.Keywords: Shape, Meaning, Naming Place, Description textAbstractThe naming of places in JawaiSub-district has its own characteristics contained the origin of the name of the place.. It is important to know the name in each place. However, not everyone who lives un other place knows the origin of name of place that has been given.Naming places is closely related to geographical and cultural conditions in each region. The naming of places is not only seen geographically and culturally, but is formed through past stories, the conditions of previous societies and the languages used in each region both Chinese, Dayak, Malay and Javanese. Therefore, to solve this problem the researcher details the problem, namely how the form and meaning of naming the place in Jawai District, Sambas Regency. the results of the study obtained 20 place name data which were grouped into seven categories, namely based on plants, geography, location, people's names, occupation, people's actions, and stories.Â Keywords: Shape, Meaning, Naming Place, Description text